Explorasi Hubungan Tingkat Pengetahuan dan Sikap Serta Persepsi Pasien Kanker tentang Perawatan Paliatif - Sitorus, Tetty H; Christina, Juliana; Musri, Musri (Journal of Telenursing (JOTING), 2024)
This study explores the relationship between knowledge attitudes and perceptions of cancer patients about palliative care in Bandung. The method used is a mixed methods study. The results of the study showed that the relationship between knowledge and emotions could be known with a p-value of 0.021, knowledge and cognitive/perceptual can be known with a p-value of 0.001, knowledge and behavior can be known with a p-value of 0.044, knowledge and attitude can be known with a p-value of 0.113. The results of the thematic analysis show four themes, namely: understanding palliative care, financial problems, losing hope and expecting support, and expecting prayer. In conclusion, there is no significant relationship between knowledge and attitude. Still, the components of attitude: cognitive/perceptual, emotional, and behavior have a significant relationship with patient knowledge of palliative care. Keywords: Cancer, Knowledge, Palliative Care, Perception, Attitude